Tourism supply chain & strategic partnerships for managing the complexity in tourism industry - Bernardino Quattrociocchi; Francesco Mercuri; Mirko Perano; Mario Calabrese (Enlightening Tourism: A Pathmaking Journal)
The paper aims to investigate the possible relationship between Tourism Supply Chain and Strategic Partnership, read as a way to reduce and better manage the complexity in Tourism Industry. This last has been analysed under multi-disciplinary approaches (economic, sociological, psychological, anthropological and geographic) to better understand its main components. A synthesis of origin of Tourism Supply Chain term was provided. VRIO framework and PEST analysis was used with the aim to better understand the strategic decision of integration the chain with a single or multiple rings. Starting from this, a theoretical framework from a holistic analysis is provided.